Yeast mitochondrial RNAP conformational changes are regulated by interactions with the mitochondrial transcription factor - Drakulic, Srdja (Oxford University Press, 2014)
Mitochondrial RNA polymerases (MtRNAPs) are members of the single-subunit RNAP family, the most well-characterized member being the RNAP from T7 bacteriophage. MtRNAPs are, however, functionally distinct in that they depend on one or more transcription factors to recognize and open the promoter and initiate transcription, while the phage RNAPs are capable of performing these tasks alone. Since the transcriptional mechanisms that are conserved in phage and mitochondrial RNAPs have been so effectively characterized in the phage enzymes, outstanding structure-mechanism questions concern those aspects that are distinct in the MtRNAPs, particularly the role of the mitochondrial transcription factor(s). To address these questions we have used both negative staining and cryo-EM to generate three-dimensional reconstructions of yeast MtRNAP initiation complexes with and without the mitochondrial transcription factor (MTF1), and of the elongation complex. Together with biochemical experiments, these data indicate that MTF1 uses multiple mechanisms to drive promoter opening, and that its interactions with the MtRNAP regulate the conformational changes undergone by the latter enzyme as it traverses the template strand.